Did the COVID-19 transform consumers’ orthodox behavior?: A systematic literature review - Pamela, Kazi Sharmin; Shams, Shahpar (Journal of Asian Business Strategy, 2024)
The study aimed to explore new aspects and dimensions of consumer behavior during COVID-19. Hence, significant changes in consumer behavior were identified, and the characteristics, similarities, and differences of these behavioral approaches were discovered to obtain the purpose. The systematic literature review was conducted using the PRISMA-ScR method, which is a systematic procedure for screening and analyzing the chosen literature. The study found four major changes in consumer behavior; panic buying (large volume, short-run), stockpiling (large volume, long-run), impulse buying (small volume, short-run), and sustainable buying behavior (small volume, long-run). Moreover, this study explored the correlations and differences among these behaviors. The authors constructed an innovative framework that examines the characteristics of panic buying, stockpiling, impulse buying, and sustainable buying behavior, drawing upon existing work in the field. As this paper explains the characteristics and underlying reason for the transformed behavior, this paper can contribute to the literature on consumer behavior during uncertain situations. This study can help marketers, government, and policymakers to understand consumer behavior changes and their causes in any emergency circumstance. Furthermore, using this study’s findings, decision-makers could develop and adopt inventory management, supply chain management, and sustainable consumption policies and strategies to address the crisis.